A general approach towards multi-faceted hollow oxide composites using zeolitic imidazolate frameworks - Wu, Renbing (2016)
To realize the various functionalities and maximize the structural advantages, hollow particles with multiple compositions and complex structures are highly desirable. However, the development of a convenient and scalable method for the synthesis of such multi-compositionally complex hollow structures remains a big challenge. Herein, we report an efficient and universal strategy to fabricate a variety of porous hollow oxide nanocomposites (Co3O4/SiO2, Co3O4/TiO2, ZnO/SiO2, and ZnO/TiO2) composed of nanosized subunits, which involves a sol–gel process to form a shell onto the dodecahedral zeolitic imidazolate framework (ZIF) template and a subsequent thermolysis-induced transformation of the template at appropriate temperatures. Such a multi-compositional hollow structure with a large surface area endows the materials with exceptional properties and performances. As an example, we demonstrated that these complex hollow oxide composites, especially the Co3O4/SiO2 hollow dodecahedra, exhibit a significantly enhanced photocatalytic performance as oxygen evolution photocatalysts.